2013
DOI: 10.1111/exd.12251
|View full text |Cite
|
Sign up to set email alerts
|

Acute irritant threshold correlates with barrier function, skin hydration and contact hypersensitivity in atopic dermatitis and rosacea

Abstract: The aim of the study was to disclose interactions between epidermal barrier, skin irritation and sensitization in healthy and diseased skin. Transepidermal water loss (TEWL) and stratum corneum hydration (SCH) were assessed in adult patients with atopic dermatitis (AD), rosacea and healthy controls. A 4-h patch test with seven concentrations of sodium lauryl sulphate was performed to determine the irritant threshold (IT). Contact sensitization pattern was revealed by patch testing with European baseline series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
78
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 12 publications
4
78
1
2
Order By: Relevance
“…In contrast, cytoplasmatic TLR2 and TLR4 expression in keratinocytes was reported (5). In inflammatory skin diseases, the disturbed physical skin barrier may influence the state of the immune barrier and vice versa (11)(12)(13). Skin infections occur more frequently in atopic dermatitis than in psoriasis.…”
mentioning
confidence: 99%
“…In contrast, cytoplasmatic TLR2 and TLR4 expression in keratinocytes was reported (5). In inflammatory skin diseases, the disturbed physical skin barrier may influence the state of the immune barrier and vice versa (11)(12)(13). Skin infections occur more frequently in atopic dermatitis than in psoriasis.…”
mentioning
confidence: 99%
“…), and SCH and TEWL alterations are associated with some skin disorders (16,17), the knowledge of their daily variation could be helpful for results interpretation. In humans, some circumstances may produce loss or attenuation of the circadian rhythms (elderly, jet-lag, shift work or light alterations), which could in turn influence sleep and skin functionality (18).…”
mentioning
confidence: 99%
“…We found that the dorsal skin of NC/Nga mice developed erythema, hemorrhage, hyperkeratosis, and showed reduced hydration in the epidermis and a significantly increased frequency of scratching when compared with the untreated Balb/c mice. An increase in skin hydration, which plays an important role in maintaining the water balance of the skin, can improve AD, while a disruption of the balance and increased dryness of skin can aggravate AD [24]. We also showed that NC/Nga mice showed significant increases in spleen and liver weights when compared with the untreated Balb/c mice (p < 0.05).…”
Section: Discussionmentioning
confidence: 82%